The effects of commercial bacterial products on macrobenthos community in shrimp culture ponds - Shishehchian, Farshad; Md Yusoff, Fatimah; Mohamed Din, Mohamed Shariff (Springer Netherlands, 2002)
This study was conducted to assess the effects of commercial bacterialproducts on the composition and abundance of macrobenthos in commercial tigerprawn Penaeus monodon culture ponds. Nine brackishwaterponds, with an area of 0.5 ha each were used for this study. Twocommercial bacterial products (T1 and T2) were applied inthree ponds each. Another three ponds served as the control. Sediment samplesfrom all ponds were analyzed for the nitrogen, phosphorus and organic mattercontents, and macrobenthos. Total nitrogen and total carbon concentrations inthe sediments of T1 were significantly lower (p< 0.05) thanT2. In addition, total nitrogen in T1 pond sediment wassignificantly lower (p < 0.05) than the control towardsthe end of the culture period. There were no significant differences in totalphosphorus amongst treatments. The study revealed the presence of four majorgroups of macrobenthos in all treatments; gastropods, bivalve, polychaetes andinsect larvae. The total density of macrobenthos in all ponds, exceptgastropods, showed a decreasing trend with the progress in culture indicatingeither predation by shrimp or deterioration of pond bottom. T1 hadsignificantly (p < 0.05) higher density of polychaetescompared to the T2 and the control.